KINEMATIC AND DYNAMIC ANALYSIS OF A HEXAPOD PRONKING GAIT ROBOT AND CONTROL ACTIONS - Soyguder, Servet; Alli, Hasan (World Scientific Publ Co Pte Ltd, 2012)
This in this study, A hexapod robot was carried out walking, running and pronking with Spring Loaded Inverted Pendulum (SLIP) model in stance phase. This is solving a natural problem in which the main goal is to enable the robot to walk, run and pronking in a stable condition regardless of the environmental conditions. In order to solve this problem, kinematic and dynamic analysis, and control actions of a hexapod robot were realized for a pronking gait in this study. In addition, the stance and flight phase dynamic structures were solved in a sequential closed loop to obtain the equation of motion for pronking gait. The hexapod robot with pronking gait was controlled by PD control algorithm. As a result, all computer simulations have shown that the proposed control actions and method are more effective and make the system control quite easy and successful.
14th International Conference on Climbing and Walking Robots and the Support Technologies for Mobile Machines (CLAWAR 2011) -- SEP 06-08, 2011 -- Univ Pierre Marie Curie, Paris, FRANCE
Keywords: Quadruped Walking Machines